Penggunaan Papan Perkalian Dalam Meningkatkan Kemampuan Operasi Hitung Perkalian Pada Siswa Tunanetra Kelas III di SLB-A YAPTI Makassar - Ardiansyah, Ardiansyah; Sulasminah, Dwiyatmi; Zulfitrah, Zulfitrah (Jurnal Pendidikan Kebutuhan Khusus, 2023)
This study examines the multiplication arithmetic operations ability of class III blind students at SLB-A YAPTI Makassar. The objectives to be achieved in this study were to find out: 1) Multiplication arithmetic operations ability in class III blind students before being given treatment, 2) Multiplication arithmetic operations ability through the use of a multiplication board in class III blind students while being given treatment, 3) Arithmetic operations ability multiplication in class III blind students after being given treatment, 4) Increasing the ability to operate arithmetic multiplication after using the multiplication board based on the results of comparisons from conditions before being given treatment to conditions during being given treatment, and from conditions during being given treatment to conditions after being given treatment to class blind students III at SLB-A YAPTI Makassar. This study uses a quantitative approach with the type of SSR research with an A-B-A design. The data collection technique used was a written test. Thus the multiplication arithmetic operation ability of students after being given treatment increased and was better than before being given treatment.